Poster Exhibitions at National Conferences: Education or Farce? - Salzl, Gabriele (Deutscher Arzte Verlag, 2008)
INTRODUCTION: The so-called poster exhibition is an established element of medical meetings which often receives little attention. The aim of this study was to analyze the organization, acceptance and value of poster exhibitions. METHODS: Interview based study conducted during the annual meeting of a German specialist medical conference. A total of 247 attendees, poster authors and „poster chairpersons“ were interviewed. Attendance at poster exhibitions was documented, the poster review and award process analyzed, and abstracts assessed for redundancy of presentation. RESULTS: Participation in poster exhibitions was very low. Despite this, their scientific value was esteemed high by young authors and the poster chairpersons. Almost a third (29.4%) of posters had been displayed at other meetings. Several attendees (55.4%) and poster presenters (49.1%) say they would welcome the opportunity for personal one-on-one discussion at the poster in addition to poster viewing. DISCUSSION: The option of additional personal discussion with the poster presenter may lead to an increase of the rather modest participation of attendees at poster exhibitions. Poster exhibitions are of value in particular for young scientists and poster chairpersons.